The Effects of Restraint and Seclusion on Patients with Mental Disorder: A Systematic Review - Imelda Manek Laku; Indah Winarni; Heni Dwi Windarwati (GoAcademica Research & Publishing, 2020)
The restraint and seclusion could worsen condition of patients with mental disorder on several aspects as physical, psychological, and social. Objective: To identify the effects or impacts of restraint and seclusion behavior on patients with mental disorder. This systematic review was initiated to identify literatures on scientific articles which have been published between 2009-2019 in three databases as ProQuest, pubmed, and Sciencedirect. The selection was conducted in PRISMA flow-diagram and criticized through JBI tool. After 10 relevant articles were collected, they would be analyzed to be a systematic review. Most of ten researches illustrated to negative effects on physical and psychosocial aspects as a consequence of restraint and seclusion on patients with mental disorder. A few of positive effects have been also felt, but was not comparable to the negative effect. The implementation of restraint and seclusion behavior could worsen the condition of patients which became a consideration for the health officer to do intervention of restrain and seclusion on patients with mental disorder.